Knowledge and Attitude on Abortion among women of Reproductive age group attending Manipal Teaching Hospital, Nepal - Adhikari, Laxmi (Europasian Journal of Medical Sciences, 2019)
Background: Abortion was legalized in Nepal in September 2002 by the amendment to the “Muluki Ain”. Legal, moral and ethical issues surrounding abortion make research on all aspects of abortion difficult to undertake. The objective of this study is to assess knowledge and attitude regarding abortion among women of reproductive age group (15-45 years). Methods: This study was a descriptive and conducted in Manipal Teaching Hospital (MTH), Pokhara, Nepal. The tools were demographic proforma, knowledge questionnaire, and attitude scale on abortion. Data was collected by asking questions regarding abortion. The total sample was 100 and the sampling technique was purposive. The data were analyzed using Excel 2007, SPSS for Windows Version 16.0 Results: The majority (83%) of the participant were of age group 15-30years, most (70%) of them were married, most (82%) of them were Hindu. The majority of the participants (95%) had heard regarding Abortion. About half (55%) got information from mass media. Most (58%) of the women are having average knowledge regarding Abortion, and the remaining 4% is having poor knowledge. The majority (90%) of the women have a good attitude and no one is having an unfavorable attitude. There is a significant association between knowledge and level of education. There is a positive correlation between knowledge and attitude. Conclusion: Though the majority of the women had a good attitude regarding abortion, still few women i.e. 4% attending MTH don’t have good knowledge.